Measurement, spatial distribution dynamics, and influencing factors of forest ecological product value realization efficiency in China - Zheng, Lin Lin; Zhang, Jing Yang; Suo, Lei; Yu, Wei Ming; Shi, Xiong Tian (Frontiers in Environmental Science, 2025)
With the intensification of global climate change and ecological issues, the efficiency of forest ecological product value realization (FEPVRE) has become crucial in driving the green economy transformation. This paper, based on the Super-SBM model, measures FEPVRE across 30 Chinese provinces from 2012 to 2022. It employs methods such as spatial kernel density estimation, Markov chain analysis, the Gini coefficient method, the gravity model, and Quadratic Assignment Procedure (QAP) to assess its spatial distribution and dynamics. Additionally, spatial econometric models are applied from the perspective of the digital economy to explore the driving mechanisms of digital technologies, industries, and the digital environment on FEPVRE. The findings show: (1) FEPVRE in China exhibits fluctuating trends, with a convergence pattern from east to west. (2) FEPVRE associations shift from the eastern to the central regions, with stronger associations in the southeast. (3) FEPVRE will continue differentiating into two levels, with type IV regions prone to “level-locking” and club convergence. (4) Uneven digital technology distribution worsens regional disparities, but digital industries and environments help narrow the gap. (5) Eastern and Northeastern regions have higher FEPVRE due to better digital infrastructure and policies, while Central and Western regions face challenges, resulting in negative spillovers. High-efficiency regions positively influence neighboring areas. To achieve a balanced and sustainable green economy, bridging the digital divide in underdeveloped regions and promoting digital industries is key. Improving digital infrastructure will enhance FEPVRE and support an inclusive green economy.